COMPASSION AND PITY: DIFFERENT MODES OF AFFECTIVE INTERACTION - Lima, Eliane Soares de (Laboratório Editorial FCL-UNESP, 2016)
From a lexical-based analysis, guided by the theoretical-methodological parameters of French Semiotics in its tensive approach, the aim of this article is to examine the points of similarity and, above all, the divergent ones in the production of the feeling of compassion or pity. In doing so, we will start with an investigation based on the dictionary entries of different Romance languages in order to infer the semes that constitute each passionate nucleus, as well as the elements of the process of discourse configuration. By unfolding the syntax structure underlying every lexeme-affection, our interest relies on understanding what determines two modes of different affective interactions – a more sensitive one, which pertains to a “feeling with”, and a more intelligible one, typical of a “feeling for” – through the same predicative scene.